USM EMERGES AS CHAMPION AGAIN IN MICPA-CAANZ ACCOUNTING STUDENTS QUIZ 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, December 2016 – A team from the School of Management (SoM), Universiti Sains Malaysia (USM) – Mavericks which comprised of Kooi Shiu Lun, Sunisa A/P Ai Som Chok and Lim Kean Wooi became the champion of the Accounting Students QuizDegree Level in conjunction with the MICPACAANZ Accountancy Week 2016 held in Universiti Kebangsaan Malaysia (UKM) recently.